Electron delocalization and dimerization in solid C59N doped C60 fullerene - ROCKENBAUER, A; CSANYI, Gabor; FÜLÖP, F; GARAJ, S; KORECZ, L; LUKACS, R; SIMON, F; FORRO, L; PEKKER, S; JANOSSY, A (Physical review letters, 2005)
Electron spin resonance and ab initio electronic structure calculations show an intricate relation between molecular rotation and chemical bonding in the dilute solid solution. The unpaired electron of C59N is delocalized over several C60 molecules above 700 K, while at lower temperatures it remains localized within short range. The data suggest that below 350 K rigid C59N-C60 heterodimers are formed in thermodynamic equilibrium with dissociated rotating molecules. The structural fluctuations between heterodimers and dissociated molecules are accompanied by simultaneous electron spin transfer between C60 and C59N molecules. The calculation confirms that in the C59N-C60 heterodimer the spin density resides mostly on the C60 moiety, while it is almost entirely on C59N in the dissociated case.